Application of Ta‘zīr Sanctions and Ta‘wīḍ Compensation in Mushārakah Mutanāqiṣah Contracts in Sharia Banking - Fauzin, Aris (Journal of Economicate Studies, 2018)
Mushārakah Mutanāqiṣah (MMQ) is one of the innovative financing schemes implemented by Sharia banking institutions, allowing joint asset ownership between banks and customers with gradual transfer of ownership. A frequent issue in MMQ transactions is the customer’s failure to fulfill payment obligations. In response, Sharia banks refer to Fatwa DSN-MUI No. 43/DSN-MUI/VIII/2004 on compensation (ta‘wīḍ) and Fatwa No. 17/DSN-MUI/IX/2000 on disciplinary sanctions (ta‘zīr). This study explores the legitimacy and application of these fatwas in the context of MMQ contracts, using a descriptive-qualitative approach through literature and documentation analysis. The findings indicate that imposition of sanctions must be aligned with the nature of the breached contract within MMQ—whether it is mushārakah, bai‘, or ijārah—to avoid unjust enforcement. The study concludes that while the fatwas provide legal grounds, a contextual contract-based analysis is crucial in applying punitive measures fairly.